Analysis of multiechelon maintenance network characteristics using implicit enumeration algorithm - Madu, C.N.; Kuei, C.-H. (Mathematical and computer modelling, 1996)
In this paper, we use Buzen's algorithm to develop models for computing network characteristics for a multiechelon repairable system with load independent servers. Buzen's algorithm is used to develop a solution technique to a closed queueing maintenance network with four nodes: operations, diagnostics, service, and scrap and replacement. A program is developed in visual Basic to compute the expected values and marginal probabilities for the nodes.